Studies of the Effects on Ostrich Growth, of Silage, Altering Feed Levels and Some Nutritional Supplements in Feed - Dube, S.; Mwenje, E.; Kambasha, E. (International Journal of Poultry Science, 2009)
In this study we tested the effect of altering ostrich feed, by adding silage to feed in the ratio 2:1, by reducing feed levels to 90% and 75%, by adding antimicrobial growth promoter Zinc bacitricin and flavoumycin and presenting probiotics as liquid and powder. For each trial a control was set up with only normal prescribed feed supplied. All the birds used were health kept under high hygiene and vaccinated and dewormed to remove interference from pathogens. The results indicated that silage improved palatability and food intake. Reducing feed levels did not significantly alter the FCR or the performance of the birds. Growth promoters increased FCR but mortality was high. Probiotics were more effective when presented in liquid form than powder. The results show that data on effectiveness of feed supplements should be extrapolated to ostriches with caution.